Investment Portfolio Optimization With Mean-Variance Investment Portfolio Optimization Model Without Risk Free Assets - Wilda Nur Rahmalia; Dwi Susanti; Rizki Apriva Hidayana (International Journal of Quantitative Research and Modeling, 2022)
Forming a portfolio is a strategy that is often carried out by investors in risky investment conditions. Five non-risk free stocks were selected, namely PTBA, IPCM, ANTM, BUMI, and ADMF. The purpose of forming this portfolio is to determine the composition of the weight (proportion) of the allocation of funds in each of these shares in forming the optimum portfolio. The method used is the Mean-Variance investment portfolio optimization model without risk-free assets using the Markowitz approach. Based on the results obtained by the optimum portfolio of the Mean-Variance model without risk-free assets, the average return is 0.00105 and the variance is 0.000067 with a portfolio ratio value of 14.65256. The proportion of fund allocation to PTBA shares = 0.28872; IPCM=0.02484; ANTM=0.00016; EARTH=0.13501; and ADMF=0.55126. It is hoped that the formation of this portfolio optimization model will be useful as an alternative for investors in optimizing the investment portfolio to make it more profitable in the future.